Perbandingan Kinerja Keuangan BPR dan BPRS di Jawa Tengah Selama Pandemi Covid-19 - Teguh Hardi Raharjo; Irwan Prasetyo; Liris Kristina (Faculty of Economics and Business, University of Pancasakti Tegal, 2021)
This study aims to compare the financial performance of Rural Banks (BPR) and Islamic Financing Banks (BPRS) in Central Java during the Covid-19 Pandemic based on aspects of capital, productive asset quality, profitability, and liquidity. This research uses descriptive quantitative method. The sample was selected using a purposive sampling method obtained 73 research samples in the quarterly period March, June, and September. Data analysis used the Mann Whitney Test which was processed through the SPSS program. The results showed that: (1) There is a significant difference between the financial performance of BPR and BPRS based on the capital aspect as measured by the KPMM ratio; (2) There is a significant difference between the financial performance of BPR and BPRS based on the quality aspect of earning assets as measured by the NPL/ NPF ratio; (3) There is a significant difference between the financial performance of BPR and BPRS based on the profitability aspect as measured by the ROA ratio, but there is no significant difference between the financial performance of BPR and BPRS based on the profitability aspect when measured by the BOPO ratio; (4) There is a significant difference between the financial performance of BPR and BPRS based on the liquidity aspect as measured by the ratio of LDR / FDR and CR. In general, the financial performance of BPR was better than those of BPRS in Central Java during the Covid-19 Pandemic.